A NUMERICAL SIMULATION OF THE WIND-DRIVEN WATER CIRCULATION ON THE SUNDA SHELF - Groves, Gordon W.; Niemeyer, Gary (Marine Research in Indonesia, 1975)
A numerical simulation of the barotropic circulation over the Sunda Shelt was carried out for a time-invariant wind field corresponding to (a) the Northwest Monsoon and (b) the Southeast Monsoon seasons. Starting from a state of rest, the current and surface configurations were timestepped until an apparent state of equilibrium was reached. The resulting current pattern and sea-surface topography are in good agreement with observations during those two seasons.